Dual function of Gasdermin E: pyroptosis-mediated pan-cancer suppression versus HCC-specific oncogenic activity - Kahaer, Gulijiamali; Pan, Sirun; Yang, Chengcheng; Xie, Wenchen; Lu, Yan (Frontiers in Immunology, 2025)
Gasdermin E (GSDME), a key executor of pyroptosis, exerts a unique dual role in tumorigenesis, acting as both a tumor suppressor and a tumor-promoting factor. Due to promoter hypermethylation, GSDME is epigenetically silenced in most solid tumors, including gastric, colorectal, and breast cancers. Its activation triggers the release of inflammatory cytokines, such as IL-1β and IL-18, enhances CD8+ T cell infiltration, and improves chemosensitivity, thereby exerting potent tumor-suppressive effects. Hepatocellular carcinoma (HCC) displays an aberrant GSDME overexpression pattern, which promotes immune suppression and resistance to anti-PD-1 therapy through pyroptosis-independent mechanisms. Notably, specific interventions can activate GSDME-mediated pyroptosis in HCC, highlighting its functional plasticity in response to microenvironmental signaling networks. Current studies face three major challenges: elucidating the mechanisms underlying GSDME overexpression in HCC, clarifying the molecular hubs of pyroptosis-independent pro-tumor pathways, and developing precision strategies to control the functional switch of GSDME. Future studies should integrate single-cell multi-omics and spatial transcriptomics to establish a novel therapeutic paradigm based on “pyroptosis immunomodulation”, advancing cancer treatment from single-target inhibition toward multidimensional “microenvironment reprogramming”.